Osteopoikilosis: a case report - Behzad Mohsenpour; Amjad Ahmadi (Journal of Medical Case Reports, 2023)
Abstract Background Osteopoikilosis, also referred to as disseminated condensing osteopathy, spotted bone disease, or osteopecilia, is a rare bone disorder. The case presented here showcases multiple disc lesions in the spine, extensive multifocal skin lesions, and positive test results for dermatomyositis and multifocal enthesopathy, accompanied by neurological symptoms. This manifestation represents a novel variant of the disease. Case presentation Our patient is a 46-year-old mosque Kurdish servant presenting with complaints of pain in the right leg, lower back, right hand, and neck. Additionally, the patient has been experiencing redness in the right buttock and ipsilateral thigh, as well as gradually expanding and stiffening skin lesions on the left shin for the past 3 weeks. Painful neck movements and a positive Lasegue test were also observed in the right leg. The patient reports pain in the right buttock accompanied by a substantial erythematous area with induration measuring 8 × 15 cm, as well as an erythematous and maculopapular lesion measuring 6 × 18 cm on the left shin. Conclusions Our patient is a 46-year-old man presenting with complaints of skin lesions and pain in the lower back, pelvis, neck, and limbs. The X-ray reveals shoulder, pelvis, knee, and ankle involvement, while spinal involvement is observed in the neck and lumbar region. Furthermore, the bone scan indicates extensive enthesopathy in various regions, a unique manifestation not previously reported in similar cases.